ANALISIS KETEPATAN KODE DIAGNOSIS PENYAKIT BERDASARKAN KODE ICD-10 PASIEN RAWAT JALAN DI PUSKESMAS PLERET BANTUL - Hery Setiyawan (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Efforts to improve the quality of services at the Puskesmas are very necessary for good medical record performance, so as to produce complete and accurate information to improve the quality of Puskesmas services. To achieve good service, competent and professional medical record personnel are needed so that they are able to classify & codify diseases or actions according to the correct medical terminology. The objectives are to identify the implementation of the diagnostic code based on ICD-10, to know the percentage of accuracy of the diagnosis code, to know the percentage of the inaccuracy of the diagnosis code and to know the factors causing the inaccuracy of the diagnosis code. The research method used is descriptive research with a qualitative approach, the design used is cross sectional. The subjects and objects of this research are 2 nurses, 1 doctor, 1 medical record officer and medical record file. Data collection techniques by conducting documentation studies, observations and interviews. Based on the results of the implementation of determining the diagnosis code at the Pleret Health Center using a list of codes that are usually commonly used and searching through google, it is not carried out in the right order using ICD 10 volumes one and three, so there are still codes that are not specific and appropriate. The conclusion from the results of the analysis is that the percentage of accuracy of the diagnosis code is 40.4% and the percentage of inaccuracy of the diagnosis code is 59.6%. The factors causing the inaccuracy of the diagnosis code are incompetent human resources, the absence of fixed SOPs related to the coding system and the use of the ICD-10 book is not optimal in coding.